2020
DOI: 10.1101/2020.05.08.20095430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Total predicted MHC-I epitope load is inversely associated with population mortality from SARS-CoV-2

Abstract: Polymorphism in MHC-I protein sequences across human populations significantly impacts their binding to viral peptides and alters T cell immunity to infection. Prioritization of MHC-I restricted viral epitopes remains a fundamental challenge for understanding adaptive immunity to SARS-CoV-2. Here, we present a consensus MHC-I binding prediction model, EnsembleMHC, based on the biochemical and structural basis of peptide presentation to aid the discovery of SARS-CoV-2 MHC-I peptides. We performed immunopeptidom… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…CTLs recognize the nonself epitopes that are presented on virus-infected cells via human leukocyte antigen (HLA) class I molecules, and therefore, the CTL-mediated antiviral immunity is HLA-restricted [reviewed in (La Gruta et al, 2018)]. Recent studies have reported the HLA-restricted SARS-CoV-2-derived epitopes that can be recognized by human CTLs (Kared et al, 2021;Kiyotani et al, 2020;Nelde et al, 2021;Schulien et al, 2021;Wilson et al, 2021). More importantly, Bert et al have recently reported that the functionality of virus-specific cellular immunity is inversely correlated to the COVID-19 severity (Le Bert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…CTLs recognize the nonself epitopes that are presented on virus-infected cells via human leukocyte antigen (HLA) class I molecules, and therefore, the CTL-mediated antiviral immunity is HLA-restricted [reviewed in (La Gruta et al, 2018)]. Recent studies have reported the HLA-restricted SARS-CoV-2-derived epitopes that can be recognized by human CTLs (Kared et al, 2021;Kiyotani et al, 2020;Nelde et al, 2021;Schulien et al, 2021;Wilson et al, 2021). More importantly, Bert et al have recently reported that the functionality of virus-specific cellular immunity is inversely correlated to the COVID-19 severity (Le Bert et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This concern stems from the fact that the durability and potency of SARS-CoV-2 vaccines is indeed partially dictated by elicited T cell immune responses. Not examining the CoV-2 T cell immunomonitoring may result in vaccines that induce short lasting humoral responses in the absence of proper T cell memory responses [15][16][17][18][19][20]. Other than healthy hosts, it is also important to analyze CoV-2-specific T cell responses in certain vaccinated sub-populations such as the elderly, and hosts who bear underlying conditions that are expected to impact the immune system such as diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…13 The correlation between MHC-I and the severity of the disease in patients with COVID-19 has been previously hypothesised. 14 The understanding of which SARS-CoV-2 epitopes are immunogenic may help advances in the development of diagnostic kits and prophylactic vaccines. An immunoinformatic approach is suitable for an initial screening, since it may predict algorithms and test for the immunogenicity of a vast quantity of peptides and alleles in a cost-effective manner, reducing the costs and time on workbench.…”
Section: Original Researchmentioning
confidence: 99%
“… 13 The correlation between MHC-I and the severity of the disease in patients with COVID-19 has been previously hypothesised. 14 …”
Section: Introductionmentioning
confidence: 99%